2013
DOI: 10.4103/0019-5545.116318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga therapy on plasma oxytocin and facial emotion recognition deficits in patients of schizophrenia

Abstract: Context:Yoga therapy has been demonstrated to be useful in treatment of negative symptoms and improving the socio-occupational functioning and emotion recognition deficits in antipsychotic-stabilized schizophrenia patients. Oxytocin has been recently implicated in social cognition deficits in schizophrenia. The effect of yoga therapy on oxytocin levels in schizophrenia has not been studied.Aims:This study aimed to assess the effect of yoga therapy on symptoms, socio-occupational functioning, facial emotion rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 25 publications
1
31
0
2
Order By: Relevance
“…To be precise, after 4 months of practicing yoga, patients showed a significant reduction in the presence of psychopathological symptoms, as well as an improvement in prosocial activity and quality of life. Similar results have also been found in other studies devoted to the above problem (Behere et al, 2011;Jayaram et al, 2013;Paikkatt et al, 2015;Talwar et al, 2010;Varambally et al, 2012). The results of a study conducted with 95 respondents (Deuskar, 2010) showed that practicing yoga nidra 8 for a month and a half significantly reduced the symptoms of stress, which was confirmed by other similar studies (Malathi & Damodaran, 1999;Potey et al, 2016).…”
Section: Yoga the Results Of Scientific Research And Mental Healthsupporting
confidence: 84%
See 1 more Smart Citation
“…To be precise, after 4 months of practicing yoga, patients showed a significant reduction in the presence of psychopathological symptoms, as well as an improvement in prosocial activity and quality of life. Similar results have also been found in other studies devoted to the above problem (Behere et al, 2011;Jayaram et al, 2013;Paikkatt et al, 2015;Talwar et al, 2010;Varambally et al, 2012). The results of a study conducted with 95 respondents (Deuskar, 2010) showed that practicing yoga nidra 8 for a month and a half significantly reduced the symptoms of stress, which was confirmed by other similar studies (Malathi & Damodaran, 1999;Potey et al, 2016).…”
Section: Yoga the Results Of Scientific Research And Mental Healthsupporting
confidence: 84%
“…У конкретном случају, након 4 мјесеца практиковања јоге пацијенти су показали значајно смањење присутних психопатолошких симптома као и побољшање просоцијалног дјеловања и квалитета живота. До сличних резултата, дошла су и друга истраживања посвећена наведеној проблематици (Behere et al, 2011;Jayaram et al, 2013;Paikkatt et al, 2015;Talwar et al, 2010;Varambally et al, 2012). Резултати истраживања спроведеног са 95 испитаница (Deuskar, 2010) указују да је практиковање јога нидре 8 у периоду од мјесец и по дана, значајно довело до смањења симптома стреса, што потврђују и друга слична истраживања (Malathi & Damodaran, 1999;Potey et al, 2016).…”
unclassified
“…Yoga elevates oxytocin levels, which can improve emotion recognition (19). YT also reduces cortisol levels and thus may have an indirect neuro protective action (48).…”
Section: Discussionmentioning
confidence: 99%
“…Yoga training is feasible for individuals with psychotic disorders (15). Some randomised controlled trials (RCTs) of yoga indicated improvements in psychopathology and social cognition in SZ (1619), although the benefits were variable (17,18,20). Like yoga, physical exercise is thought to benefit cognitive functions in persons with or without psychiatric disorders (2126).…”
Section: Introductionmentioning
confidence: 99%
“…The NIMHANS studies focussed on symptom control, quality of life, social functioning (Duraiswamy et al, 2007; Varambally and Gangadhar, 2012; Jayaram et al, 2013; Gangadhar, 2014; Talwadkar et al, 2014). Talwadkar and colleagues conducted a randomized controlled study in elderly and studied the effects of Trataka in comparison with wait listed patients (Talwadkar et al, 2014 from Gangadhar, 2014).…”
Section: Yoga As Cognitive Enhancement Therapymentioning
confidence: 99%